The Legality of Provoked Abortion Due to Rape: A Human Rights Perspective - Tan, Winsherly; Fitri, Winda; Putri, Shelvia Agustini (Sultan Jurisprudence: Jurnal Riset Ilmu Hukum, 2024)
The issue of abortion is currently still an actual discussion, both done in accordance with applicable regulations and done illegally, for example, women who are victims of rape.  The purpose of this study is to explain the discussion of Abortus Provocatus as a result of acts of rape based on human rights. Based on Law Number 17 of 2003 concerning Health and Law Number 39 of 1999 concerning Human Rights and the writing of this research article using normative research methods, using library materials as data to analyse the problems discussed in the preparation of this research article. Exceptions to abortion Article 60 paragraph (2) point c which provides relief for abortion for women who are victims of rape. This is also in line with Law No. 39/1999 on Human Rights abortion is only done to protect the life of the mother and child. The existence of regulations that legalise abortion is solely to fulfil the rights and freedom of the mother from psychological and social burdens and freedom in her life as a living being that has human rights